Analisis Derajat Pengembangan Hidrogel Komposit Polivinil Alkohol (PVA) Yang Dimuat Ekstrak Daun Kirinyuh (Eupatorium odoratum) - Agung, Bertolomeus Haryanto; Suban, Maria Enjelina (LP. Ma'arif Janggan Magetan, 2024)
PVA/EDK (Kirinyuh/Eupatorium odoratum Leaves) composite hydrogel has been successfully developed using the freeze-thaw method. The precursor solution was prepared by dissolving PVA with a concentration of 12 wt% in water. Kirinyuh leaf extract solution (10 wt%) was then added to the precursor with a ratio of 10:0, 10:1, 10:2, and 10:3. The composite hydrogel was then fabricated using the freeze-thaw method and then the characteristics of the swelling degree and density were investigated. The purpose of this study was to explore the swelling degree of the Polyvinyl Alcohol (PVA) Composite hydrogel loaded with Kirinyuh Leaf Extract (Eupatorium odoratum). The research method used in this paper is a quantitative approach. The results showed that the density of the resulting hydrogel decreased with the addition of EDK mass, while the swelling degree increased with the increase in EDK mass. PVA hydrogel has an expansion degree of (187.05±7.36) %, while the expansion degree of composite hydrogel for PVA:EDK ratio (10:1), (10:2), and (10:3) is (209.60±30.90) %, (219.73±13.72) %, and (231.11±15.03) %. These results indicate that the degree of expansion of the PVA/EDK hydrogel produced has met the requirements for use as a wound dressing. However, for further development, further tests are needed such as tensile tests, porosity tests, morphology tests and antibacterial tests of the hydrogel for further applications.